Post-Irradiation Mechanical Properties Prediction of Al 6070 of MTR-Fuel Bundle for Cutting Process - Antonio Gogo Hutagaol; Imam Hidayat; Maman Kartaman Ajiriyanto; Supaat Zakaria (Universitas Mercu Buana, 2022)
The Al 6070 is the side plate material of the MTR-fuel plate bundle. These post-irradiation mechanical properties will be used in the side plate cutting process to obtain certain plates from the MTR-fuel plate bundle. This activity is part of a series of post-irradiation test processes from the MTR-fuel plate bundle in order to determine its performance. After testing in the form of a bundle (assembly), then continued testing of certain plates from the bundle. Disassembly of the plate is carried out by cutting along the two side plates (aluminum alloy) that clamp the plate. The mechanical properties of the workpiece material are important factors that affect the conditions of the machining (cutting) process. Prediction of post-irradiation mechanical properties was carried out using the change percentage of before and after irradiation of other aluminum alloys. The prediction carried out with the Si transmutation as the dominant one affects the post-irradiation mechanical properties changes in aluminum alloys. The change percentage added the mechanical properties of the pre-irradiated side plate material of the MTR-fuel plate bundle. Pre-irradiation testing of the Al 6070, namely chemical composition tests, pre-irradiation mechanical properties tests, including hardness tests (micro), and tensile tests (max stress, yield stress, and % elongation). Prediction of changes in mechanical properties of side plate material (aluminum alloy, Al 6070) before irradiation, compared to after irradiation is: hardness value from 98.51 to 127 (gf/µm2), tensile strength from 265.371 to 398 (N/mm2), the yield strength from 204.2 to 306 N/mm2.